Review of freshwater zooplankton diversity in Indian reservoirs (Zoological Records and Reviews, 2022)
Freshwater reservoirs constitute one of India's most extensive and ecologically significant aquatic habitat types, with over 5,000 large and medium reservoirs providing water for irrigation, municipal supply, and hydropower generation.Zooplankton communities in these systems serve as critical trophic links between primary producers and fish, regulatephytoplankton biomass through grazing, and contribute substantially to nutrient cycling. Despite this ecologicalimportance, the zooplankton diversity of Indian reservoirs remains poorly synthesised, with published surveys scatteredacross regional journals spanning six decades. This review synthesises published data on zooplankton species richnessand community composition from 87 Indian reservoirs documented in 146 studies published between 1960 and 2021,covering all major biogeographic zones. A total of 624 zooplankton taxa are recorded across reviewed studies,comprising 284 Rotifera, 196 Cladocera, 88 Copepoda, and 56 Protozoa and other microzooplankton. Species richnessper reservoir ranged from 18 to 124 taxa, with highest richness in peninsular reservoirs of the Western Ghats foothills.Trophic state, water retention time, and catchment land use are identified as primary determinants of zooplanktoncommunity composition. Eutrophication, driven by agricultural and urban runoff, is the dominant threat to zooplanktondiversity, promoting cyanobacteria-tolerant rotifer dominance at the expense of large-bodied cladocerans. Conservationand management recommendations for maintaining zooplankton diversity in Indian reservoirs are presented.